Visible spectroscopy of highly charged tungsten ions with the JET charge exchange diagnostic. (2nd December 2021) - Thorman, Alex; Litherland-Smith, Edward; Menmuir, Sheena; Hawkes, Nick; O'Mullane, Martin; Delabie, Ephrem; Lomanowski, Bart; Fontdecaba, Josep Maria; Scully, Shane
Abstract: Since the installation of the ITER-like wall on the JET tokamak, visible emission from a broad range of tungsten charge states has complicated plasma ion temperature and toroidal rotation measurements. A plethora of charge exchange transitions, from ions up to W 56+, and 21 suspected magnetic dipole transitions have been observed. In particular W 39+ and W 46+ charge exchange emission contaminates the long-established carbon measurement at 529 nm. Fortunately the wavelength and relative intensity of the tungsten charge exchange lines is predictable and their influence can be mitigated when they are included in the spectral fit. Neon based charge exchange measurements at 525 nm are now preferred on JET since the ITER-like wall, however in this case an unidentified tungsten magnetic dipole transition contaminates the spectrum when the electron temperature is low.